Bioethanol Production From Tapioca Solid Waste In A Batch Reactor - Soeprijanto; Siti Wulandari; Mohamad Dwi Alfaridzi (IPTEK The Journal of Engineering, 2022)
Tapioca solid waste is a by-product of processing tapioca flour in the form of dregs and contains a lot of carbohydrates which can be developed benefits by treating the waste through an enzymatic process by hydrolysis as bioethanol. Bioconversion technology is an enzymatic conversion of materials by hydrolysis which can be used to increase the value of tapioca solid waste. The purpose of this research is to convert starch from solid waste of tapioca flour industry into bioethanol through enzyme hydrolysis and fermentation processes. This study was conducted to determine the effect of the ethanol content produced from the concentration of 50 gr/l, 100 gr/l, and 150 gr/l waste of tapioca concentrations with 10ml, 15, and 20ml enzymes. The cassava samples were hydrolyzed using Alpha-amylase enzymes with various concentrations of 10ml, 15, and 20ml and 10ml Glucoamylase enzymes. In the liquefaction process, glucose content is analyzed every 30 minutes for 2 hours, then in the saccharification process, glucose content is analyzed every 30 minutes for 3 hours. The acid hydrolyzate solution was adjusted to pH 4.5 and then fermented for 3 days and analyzed every 12 hours. From the results of the study, it was found that the optimal treatment variable was the concentration variable of 150 gr/l waste of tapioca (solid waste tapioca flour) with a concentration of 20 ml of Alpha-amylase enzyme. The ethanol content obtained from the fermentation process is 3.98% (v/v).